'Komin Tipu Komin': Elit Lokal dalam Dinamika Otonomi Khusus dan Pemekaran Daerah di Papua - I Ngurah Suryawan (Jurnal Ilmu Sosial dan Ilmu Politik, 2011)
Local political contestation in Papua during the past decade were very dynamic, especially after the implementation of special autonomy, followed by the establishment of new government units in various parts of Papua. In the wave of political contestation, the identity and cultural background has become the dominant variable. This article observes the role of local elites in managing the identity issues in the midst of political contestation in the case of new government creation, by taking the example of the establishment of Manokwari as the capital of West Papua. The author indicated that some local elites tend to manipulate the cultural identity for personal gain on behalf of the public interest.